Autonomous gathering of livestock using a multi-functional sensor network platform - Marek Doniec; Detweiler, C.; Vasilescu, L.; D.M. Anderson; D. Rus (Hot Topics in Embedded Networked Sensors, 2010)
In this paper we develop algorithms and hardware for the autonomous gathering of cattle. We present a comparison of three different autonomous gathering algorithms that employ sound and/or electric stimuli to guide the cattle. We evaluate these algorithms in simulation by extending previous behavioral simulations for cattle.  We implemented one of these algorithms and present data from experiments in which cattle were equipped with sensor nodes that allowed cueing with sound and electric stimuli. We discuss the minimum requirements for algorithms and hardware for autonomous gathering.